Menara Hap Seng 2 Wilayah Persekutuan Kuala Lumpur / Ahmad Atiq Aiman Junoh ... [et al.] - Junoh, Ahmad Atiq Aiman; Muhamad Nawawi, Muhamad Ammar Zulhusni; Amido, Anis Nazira; Kamaruzaman, Ahmad Syahmi; Rahmat, Norhafizah (Universiti Teknologi Mara, Perak, 2016)
Menara Hap Seng is a prestigious commercial office build ing with lifestyle component. Menara Hap Seng is the refurbishment of the old MUI Plaza. Each floor is designed to be functional floor set within the highly desirable and internationally acclaimend Golden Triangle of Kuala Lumpur., the 2009 winner of the F IABCI Malaysia Property Award ( Office Development Category) is flanked by the majestic KLCC Twin Tower., the eminent KL Tower and the bustling presence of Bukit Bintang. In addition, Menara Hap Seng is conveniently located within the variety of Shangri La Hotel, IMC Office building, UBN Tower, The Weld and Hap Seng Star’s Mercedes Benz Autohaus. After a few years, Menara Hap Seng 2 has been built as a prestigious 31 storey “Grade A” commercial office building, Menara Hap Seng 2 is designed to be a green building with retail component set within the nightly desirable and internationally acclaimed Golden Triangle of Kuala Lumpur, Menara Hap Seng 2 is flanked by the Majestic KLCC Twin Tower, the eminent KL Tower and bustling presence of Bukit Bintang. Seamle ssly connected to Menara Hap Seng via connecting a bridge to its retail podium. Menara Hap Seng 2 provides the much needed additional corporate office and retail floor space to the city central business district.